Peningkatan Kualitas Jaringan Distribusi Tegangan Menengah Dengan Optimasi Konfigurasi - Naibaho, Rizky Jefry; Sukma, Dian Yayan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Optimalitation of distribution line configuration on 20 Kv case for reconfiguration of distribution line without changed load sytem but with setting or regulate of switch in the feeder. In this case purpose is reduce losses in feeder.In this case, did in IEEE 69 bus type distribution line analysis that consist of 1 head transformer from relay station, 73 of lines, 5 of tie lines, 69 switch and 8 lateral.Keywords : Optimalitation,Distribution Line, Configuration.